Impacto del método SSRM para la comprensión lectora en estudiantes de 1° de secundaria de la I.E. Experimental UNAP 2019 - Cabezas Rivas, Fiorella Mireya (2021)
The present investigation was aimed to solve the following research question: Which is the impact of the SSRM method for reading comprehension of 1st level students at “Experimental UNAP School”, in Iquitos. The objective was to evaluate the impact of the SSRM method for reading comprehension of 1st level students at “Experimental UNAP” school, in Iquitos. The type of research was experimental, with pre-test - post-test and control group. This corresponds to a design study: experimental experiments "pure". The population was made up of 26 students of the high school at “Experimental UNAP”, and was divided into two groups (experimental and control). The sample was composed by 13 students in this high school. The results allow us to conclude that the application of the SSRM method have a positive impact for reading comprehension. The results of the application allow us to conclude that there is a significative impact for reading comprehension of 1st level students at “Experimental UNAP” 2019.